Kualitas Layanan Pondok Pesantren Modern dan Rumah Tahfidz Al-Ikhwan Assalam - Fitriani Nasution; Rani Febriyanni; Endah Retno Suci; Irma Sari Ramadhani (Transformasi Manageria: Journal of Islamic Education Management, 2023)
This study aims to determine the quality of services at Modern Islamic Boarding Schools and Tahfidz Al Al Ikhwan Assalam Houses which include educators and education staff, curriculum services, facilities and infrastructure, and financing. This type of research is descriptive qualitative research. Al Ikhwan Assalam Islamic Boarding School has tried to improve the competence of educators and education staff by providing trainings in improving their competence and sending teachers to various trainings held by educational institutions that specialize in teaching education science. Al Ikhwan Assalam Islamic Boarding School uses a modern Islamic boarding school curriculum which includes religious learning and general lessons. Al Ikhwan Assalam Islamic boarding school has complete facilities and infrastructure. The facilities and infrastructure include Islamic boarding schools, classrooms, student dormitories, libraries, prayer rooms, rooms for certain activities, fields, and other learning support facilities such as blackboards, stationery, desks, projectors and others. The Al Ikhwan Assalam Islamic Boarding School has good financial management where the income and expenses are transparent and the administration is clear. Of course this can affect the course of a management in the Islamic boarding school. Because if there are problems related to finance, it can also affect the management process and the learning process. Keywords: service quality, modern Islamic boarding school, tahfidz house, Al Ikhwan Assalam